2006
DOI: 10.1017/s1049096506060707
|View full text |Cite
|
Sign up to set email alerts
|

Field Research Methods in the Middle East

Abstract: In recent years, a growing chorus of voices in the political science discipline has become concerned with the balance among alternative methodological approaches in empirical research and publications. Accordingly, these scholars have issued a call to further develop and refine rigorous methods for qualitative studies, in contrast to studies that rely on quantitative methods and formal modeling (Bennett, Barth, and Rutherford 2003; Yanow 2003; George and Bennett 2005). My own interest and reason for cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 1 publication
2
53
0
Order By: Relevance
“…Little is in fact known about what drives fieldwork choices. Clark's (2006) valuable survey of difficulties faced by researchers in the Middle East and North Africa only showed 16% of respondents specifying 'the political situation' and safety as contributing to their country choices, and did not distinguish between repression and other safety risks. A more recent study on the political risks of field research in Central Asia found that '(s)everal respondents reported that they no longer work in Uzbekistan' and a 'few respondents singled out Turkmenistan and Azerbaijan as sites where they have experienced significant censorship/restrictions, chosen not to go, or experienced difficulty going'(CESS 2016, 7).…”
Section: Constrained Choicesmentioning
confidence: 98%
See 1 more Smart Citation
“…Little is in fact known about what drives fieldwork choices. Clark's (2006) valuable survey of difficulties faced by researchers in the Middle East and North Africa only showed 16% of respondents specifying 'the political situation' and safety as contributing to their country choices, and did not distinguish between repression and other safety risks. A more recent study on the political risks of field research in Central Asia found that '(s)everal respondents reported that they no longer work in Uzbekistan' and a 'few respondents singled out Turkmenistan and Azerbaijan as sites where they have experienced significant censorship/restrictions, chosen not to go, or experienced difficulty going'(CESS 2016, 7).…”
Section: Constrained Choicesmentioning
confidence: 98%
“…These things have not happened to us. Clark's (2006) survey, mentioned above, despite the modest number of responses (55) gives some insight into the frequency of such events, at least in the Middle East and North Africa: '22% of the researchers noted that they at one point had difficulties gaining entry to the countries of research or obtaining research visas due to the perceived political sensitivity of their topics by the host governments. Others reported that they had experienced the threat or actual seizure of their research data (5%), surveillance and monitoring by security (4%), arrest and/or detention (4%), and police harassment (2%)'.…”
Section: Not So Dangerousmentioning
confidence: 99%
“…Cohen and Arieli (2011) describe how a conflict environment can make it extremely difficult to locate, access and involve members of the population. A survey on the difficulties of conducting qualitative research in authoritarian or semiauthoritarian states in the Middle East by Clark (2006) found that most problems were related to the political climate, which in turn complicated access to the local population.…”
Section: Data Availabilitymentioning
confidence: 99%
“…The literature on qualitative research methods has mostly focused on conducting research on democratic states, with little attention being directed to the challenges of undertaking research on authoritarian states (Clark, 2006). This gap in the literature is especially significant for social scientists whose research in repressive regimes may involve interview and survey design research methods, which might have methodological and ethical implications for accessing participants.…”
Section: Introductionmentioning
confidence: 99%
“…Clark (2006), in a qualitative research study which involved surveying political scientists conducting research in the Middle East, found that there were three issues that concerned political scientists: (1) They claimed that the most significant challenge was the authoritarian and political situation in Middle Eastern societies; (2) They asserted that the nature of the political regime limited the choice of countries for research, prompting re-evaluation of interviewing techniques, and creating serious ethical issues for researchers; and (3) They emphasized the significance of properly trained researchers in conducting fieldwork in such a context. The recommendation was to train researchers on the actual aspects of fieldwork, such as interview techniques and the formation of questions in the context of an authoritarian state.…”
Section: Introductionmentioning
confidence: 99%